The effects of trunk occlusion in video-based projection on the visual search behavior of elite Silat athletes - Sim, Kai Xiong (Nanyang Technological University, 2021)
This study investigated the Visual Search Behaviour (VSB) of elite Silat athletes responding to Silat specific attacks in Non-Occluded and Occluded conditions. Occlusion refers to the spatial occlusion of the trunk of a video-projected opponent. It was hypothesized that (i) there would be higher number of fixations in occluded conditions and (ii) despite occlusion, the trunk will remain the primary fixation. Seven Male elite Silat athletes were recruited. They were tested via stereoscopic projection system. VSB and Quiet Eye (QE) variables were coded according to 11 areas of interest (AOI), collected using the Dikablis V3 mobile eye tracker. Significant differences were found with 14% less fixations during occlusion regardless of attack. Left Roundhouse Kicks also had 9.6% higher fixation duration than Right Sidekicks. During comparisons between AOI, the occluded conditions showed higher overall fixation on the trunk as 7 variables had significantly higher values in the trunk compared to only 3 variables in non-occluded conditions. The results indicated fewer but longer fixations and higher fixations on the trunk than other AOIs. This suggests trunk occlusion decreased the need for visual scanning and increased use of the trunk as a visual pivot. Therefore, this study reiterates the trunk as the primary fixation found in previous studies on VSB of elite Silat athletes. Also, findings suggests that occlusion may be used as a training tool for sub-elite athletes, cueing them to reduce cognitive load on less crucial information and increase trunk fixation, mimicking the VSB of elite athletes thus potentially improving performance.